2019
DOI: 10.2147/dddt.s212491
|View full text |Cite
|
Sign up to set email alerts
|

<p>The safety, pharmacodynamics, and pharmacokinetics of immediate-release formulation containing esomeprazole 20 mg/sodium bicarbonate 800 mg in healthy adult male</p>

Abstract: Background Esomeprazole is the most effective treatment for acid-related disorders and is widely used with enteric coating due to rapid degradation in the acidic environment. However, the enteric-coated formulation delays absorption and onset of action. To overcome this limitation, an immediate-release formulation containing esomeprazole 20 mg and sodium bicarbonate 800 mg (IR-ESO) was developed. Purpose To evaluate the safety, pharmacokinetics (PK), and pharmacodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…This trend was observed both after a single- and multiple-dose at steady state and in other fixed dose combinations of PPIs and NaHCO 3 . 14 , 15 Previous studies indicated that the gastric emptying rate increases as the size of the non-disintegrating drugs gets smaller. 22 , 23 Similarly, formulations developed for faster disintegration compared to the conventional ones showed a more rapid absorption in several clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This trend was observed both after a single- and multiple-dose at steady state and in other fixed dose combinations of PPIs and NaHCO 3 . 14 , 15 Previous studies indicated that the gastric emptying rate increases as the size of the non-disintegrating drugs gets smaller. 22 , 23 Similarly, formulations developed for faster disintegration compared to the conventional ones showed a more rapid absorption in several clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Percent decrease from baseline in the integrated acidity was used as a parameter for comparing the PD effects in previous studies. 15 , 16 , 34 It compares the acidity of the baseline and after a single- or multiple-dose. Considering that only about 2/3 of the proton pumps are inhibited after a single PPI dose, anticipation of the variability of the parameter after a single-dose was expected to be demanding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations